Long-term follow-up on Cushing disease patient after transsphenoidal surgery - Insook Jeong; Moonyeon Oh; Ja Hye Kim; Ja Hyang Cho; Jin-Ho Choi; Han-Wook Yoo (Korean Society of Pediatric Endocrinology, 2014)
Cushing disease is caused by excessive adrenocorticotropic hormone (ACTH) production by the pituitary adenoma. Transsphenoidal surgery is its first-line treatment. The incidence of Cushing disease in children and adolescents is so rare that long-term prognoses have yet to be made in most cases. We followed-up on a 16-year-old male Cushing disease patient who presented with rapid weight gain and growth retardation. The laboratory findings showed increased 24-hour urine free cortisol and lack of overnight cortisol suppression by low-dose dexamethasone test. The serum cortisol and 24-hour urine free cortisol, by high-dose dexamethasone test, also showed a lack of suppression, and a bilateral inferior petrosal sinus sampling suggested lateralization of ACTH secretion from the right-side pituitary gland. However, after a right hemihypophysectomy by the transsphenoidal approach, the 24-hour urine free cortisol levels were persistently high. Thus the patient underwent a total hypophysectomy, since which time he has been treated with hydrocortisone, levothyroxine, recombinant human growth hormone, and testosterone enanthate. Intravenous bisphosphonate for osteoporosis had been administered for three years. At his current age of 26 years, his final height had attained the target level range; his bone mineral density was normal, and his pubic hair was Tanner stage 4. This report describes the long-term treatment course of a Cushing disease patient according to growth profile, pubertal status, and responses to hormone replacement therapy. The clinical results serve to emphasize the importance of growth optimization, puberty, and bone health in the treatment management of Cushing disease patients who have undergone transsphenoidal surgery.